THE INFLUENCE OF USING MAKE A MATCH TECHNIQUE TOWARDS STUDENTS’ SPEAKING ABILITY - Puspa, Titi; Dede Imtihanudin; Eneng Liah Khoiriyah (Cakrawala Pedagogik, 2023)
This research is aimed to know the influence of using make a match technique towards students’ speaking ability at Eight Grade of SMPN 3 Kaduhejo. The researcher would like to find the formulation of the problem about Speaking Ability at eight grades of SMPN 3 Kaduhejo.  In this research, researcher used Quantitative research in implementing the quasi experimental design as the research method. The sample that was used in this research was the students of VIII A as the experimental class and VIII B as the control class. Researcher used 47 students as a sample from both of classes. Researcher used SPSS Version 25 to find out the result Pretest and Posttest. Based on the result of the research there was a positive influnece towards students speaking ability which was taught by applying make a match technique. It can be seen from the result of independent samples test that students who were taught by using Make a Match Technique. (experimental group) got score 0.002 which the hypothesis if the score lower than 0.05 then Ha is accepted. Meanwhile, for determining the result of students’ average score from the same group, the researcher decided to use paired samples test. The result showed that alternative hypothesis is accepted because the result of paired samples test was 0.000 which lower than 0.05.